Minority Media: Media of Transnational Identities - Zran, Jamel; Ben Messaoud, Moez; Miladi, Noureddine (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to analyze minority media as a discourse reflecting cultural and identity diversity in modern societies, by examining its role in shaping or weakening transnational identities. It focuses on the contribution of traditional and digital media to building a cross-border communicative identity among minorities, addressing their representation in the media and the relationship between media and minorities in terms of connection and isolation. The study also traces the shift from local media to transnational digital media and compares minority presence in Western and Arab media, explaining the limited Arab interest in this phenomenon despite its development in Western contexts. Methodology: The researcher adopted an inductive analytical approach to trace the historical development of minority media and analyze its theoretical discourses, alongside a comparative method between European and Arab experiences. Applied models were analyzed, including Moroccan migrant media in France, digital platforms of Arab diasporas, and media of sectarian and linguistic minorities. Results: The results show that minority media has evolved from traditional to digital forms, giving rise to concepts such as the “connected migrant” and the “virtual homeland” Media now plays a dual role between empowering minorities and reinforcing stereotypes. It was also found that 75% of minority media in Europe is digital and is mostly presented in the host country’s language, producing a hybrid local transnational identity. In contrast, Arab interest in this field remains limited due to political considerations, despite the multiplicity of minorities. Conclusion: The study concludes that minority media has become a space for forming identities that transcend the nation-state, combining empowerment and exclusion through granting recognition or reproducing marginalization. It emphasizes the need for media based on diversity and justice, supported by legislation that ensures fair representation of minorities without distortion, and calls for deeper Arab studies to understand communicative transformations in the era of digital globalization.